2006
DOI: 10.1007/s00335-005-0161-5
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 2 locus Nidd5 has a potent effect on adiposity in the TSOD mouse

Abstract: We previously reported a quantitative trait locus for body weight, non-insulin-dependent diabetes 5 (Nidd5), on Chromosome 2 in the TSOD (Tsumura, Suzuki, Obese Diabetes) mouse, a model of polygenic obese type 2 diabetes. To find the gene responsible for a specific component of the pathogenesis, we used a marker-assisted selection protocol to produce congenic strains. These mice are designed to carry a control BALB/cA-derived genomic interval and a TSOD background to look for loss of phenotype. One of the stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…16,17) In our experiments, the TSOD mice showed significant accumulation of visceral fat, and developed metabolic disorders including glucose intolerance, hyperlipidemia, hypertension, hyperinsulinemia and peripheral neuropathy. This was in sharp contrast to the TSNO control group.…”
Section: Tionmentioning
confidence: 68%
“…16,17) In our experiments, the TSOD mice showed significant accumulation of visceral fat, and developed metabolic disorders including glucose intolerance, hyperlipidemia, hypertension, hyperinsulinemia and peripheral neuropathy. This was in sharp contrast to the TSNO control group.…”
Section: Tionmentioning
confidence: 68%
“…A previous study mapped an overlapping QTL Mob that confers increased adiposity in F2 (C57BL6/J × CAST/Ei) mice inheriting chromosomal regions from B6 and lower adiposity in mice inheriting the CAST chromosomal region ( 39 , 40 ). Conversely, BALB/c alleles of Nidd5 on chromosome 2 have been shown to decrease obesity in Tsumura Suzuki obese diabetic (TSOD) mice ( 41 ). Underlying mechanisms were not described; however, analysis of lipolysis in those models would indicate whether a common locus was involved in obesity resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of a sole QTL have been verified using congenic mice (Mizutani et al, 2006;Stoehr et al, 2004), but the responsible gene has not been identified for a long time. Recently, the novel diabetic modifier gene Sorcs1 was identified from QTL on chromosome 19 using sub-congenic as well as congenic mice derived from C57BL/6 and BTBR strains (Clee et al, 2006).…”
Section: Introductionmentioning
confidence: 99%